Penerapan Metode VIKOR dalam Pemilihan Penyedia Barang/Jasa - Putri, Handayani Metha (LPPM STIKOM Tunas Bangsa, 2023)
As a company operating in the mining sector, PTBA UPO opens up opportunities for other companies to provide the needs and requirements of their companies. To make it easier to select goods/service providers, a decision support system is needed that will help the selection process more quickly and precisely. The decision support system will provide recommendations according to the desired criteria. Recommendations are obtained using the VIKOR method using criteria in the form of product quality, guarantee and offer price. The Victor method is used because it has ranking results that are closest to the ideal solution. With the lowest calculation result, namely 0, alternative 2 is the best alternative recommended as a provider of goods/services.